Development of PJBL based Rhythmic Gymnastics Learning using the Padlet Platform in Physical Education - Angga Teja Permana; Resty Gustiawati; Ega Trisna Rahayu; Ruslan Abdul Ghani; Rolly Afrinaldi (UNIB Press, 2024)
In this modern era, education has become a basic need for every individual. In fact, the government requires that its citizens have the right to receive education for 12 years and it is recommended that more than that. Development of PjBL based rhythmic gymnastics learning using the Padlet Digital Platform in physical education which has been systematically structured according to the ability level and characteristics of vocational school students based on the results of needs analysis in the field. Therefore, the development of PjBL-based rhythmic gymnastics learning using the Padlet Digital Platform in physical education learning for Kajuruan Middle School students can be declared very feasible to be applied in physical education, sports and health learning in middle schools to better achieve the predetermined learning goals. effectively. From the results of the frequency distribution value of the Implementation suitability assessment with a percentage of 88.4%, it can be concluded that the Implementation value received a